Diet Quality Is Low and Differs by Sex in People with HIV. Issue 1 (9th January 2019) - Weiss, Julian J; Sanchez, Laura; Hubbard, Jane; Lo, Janet; Grinspoon, Steven K; Fitch, Kathleen V
ABSTRACT: Background: People with HIV (PWH) are at risk for developing metabolic comorbidities driven, in part, by immune activation/inflammation. Little is known about diet quality, a potential modifiable factor in PWH. Objectives: This study aimed to explore diet quality in terms of conformance with US dietary guidelines by calculating Healthy Eating Index-2010 (HEI) scores among adults with and without HIV in Boston, MA, and determine associations with HEI and markers of immune activation/inflammation. Methods: One-hundred and three HIV-infected [50 women, 53 men; mean ± SD age: 47 ± 7 y; body mass index (BMI, in kg/m 2 ): 26 ± 5] and 38 uninfected adults (17 women, 21 men; age: 46 ± 7 y; BMI: 28 ± 4) were included in this cross-sectional analysis. Participants who completed a 4-d food record from which HEI could be calculated were included. HEI was compared between participants with and without HIV, within HIV-infected participants stratified by sex, and by HIV serostatus and sex. In the HIV group, predictors of HEI were determined in multivariable modeling. Univariate associations with diet quality and inflammation/immune markers were assessed. Results: The HEI score was 51.3 in the HIV-infected participants and 57.3 in the HIV-uninfected participants ( P = 0.052). In the comparison by HIV serostatus and sex, HIV-infected women had significantly lower HEI (49.2) compared with HIV-infected men (55.7) ( P = 0.005) and HIV-uninfected men (61.8) ( P = 0.002). Adjusting for potential confounding factors, sex remained an independent predictor of HEI in HIV ( P = 0.02). In the HIV group, higher log HEI was associated with lower concentration of the immune activation marker sCD14 ( P = 0.009). Conclusions: Diet quality tended to be lower in HIV-infected individuals compared with HIV-uninfected individuals and was lower among HIV-infected women compared with HIV-infected men, and HIV-uninfected men. There may also be an association with diet quality and sCD14 in PWH. Future prospective studies are needed to confirm these findings and determine whether improving diet quality is a useful strategy to reduce metabolic abnormalities in this population. This study was registered at clinicaltrials.gov as NCT00455793.